Open University Malaysia's Market Driven Approach in Fulfilling Varying Needs of Adult Learners - Shaari A. Hamid (2008)
Open University Malaysia (OUM) is only in her seventh year of operations, but she has carved a niche in an increasingly competitive market. With a mere enrollment of 721 when she first open her doors in August 2001, the corresponding figure stood at 65,384 students in September 2007, recording a compound growth rate of about 40 percent per annum. In terms of geographic concentration, apart from the capital city of Kuala Lumpur and its vicinity, other exceptionally high growth areas are the marginalized populace of the states of Kelantan, Sarawak and Sabah. She has also sailed beyond - to Bahrain, Yemen and islet of Indonesia. Negotiations are also underway for her programs to be offered in a couple of other countries which had learnt of OUM's mark in her expressed market.